Tribology of elastomers - Zhang, Si-Wei (Tribology and interface engineering series ;, 2004)
In spite of the practical importance of the friction, wear and lubrication of elastomers, limited literature is available on this topic. Addressing these needs, this book will give readers a complete understanding of rubber tribology and the key developments in this field over the last ten years. For the first time new and important achievements such as theories of rubber abrasion and surfacial mechanochemical effects of rubber wear are presented. The book pays special attention to the principles of rubber wear a clear understanding of which is essential for those striving towards further increasing the working life of rubber. * Comprehensively and systematically covers main points of rubber tribology * The original choice of contents informs readers of the latest developments in the field *Meeting the needs of various readers - researchers, engineers, technicians, graduates.